POTRET MASALAH SOSIAL DALAM ANTOLOGI PUISI KONSER KECEMASAN - Siti Haryawati (STKIP Paris Barantai, 2016)
Literature is a picture or portrait of life. The elements, which are contained in the literature is a reflection of life. It exists in the society reflects some conflicts in that society. Thus, the creation of a literature by an author direelty or not is the attitude freedom of an author towards the things that happened. Social Issues are an interesting theme to be used as a poetry anthology, especially if it is written by the environmental poet groups. A poet illustrates the social issues in Banjar Society clearly. Hence, there are many social issues that cause anxiety in this anthology. Therefore, the phenomena of social issues in the poetry anthology ofKonser Kecemasan which to find in this reseach. The method that is used in this research is literature study with a qualitative descriptive approachby using contcert analysies which is contained in a poetry anthology of Konser Kecemasan by starting reads critical data sources in the Poetry Anthology ofKonser Kecemasan, then read continually and appreciate the data source in Poetry Anthology of Konser Kecemasan. Moreover, the researcher reads reviewing the data sources to give the sign in the parts of the text in Poetry Anthology of anxiety concert which was appointed and analyzed the data further. Based on the analysis result of Poetry Antologi of Konser Kecemasan, there weresame mostly social issues reflected in that poetry such as poverety, crime, enviroumental and bureaucratic. The issues covered by the there of anxities realistic, moral, and neurotic. The dominant off all is moral anxiety. It was caused by the environmental and criminal problems. The environment was effected by the crime of grouping authority. An in of active bureaucrecy to pose poverty problem. The effect of realistic anxiety is followedby thr moralanxiety which is the fear of dangers will be faced. Keywords: Social issues, Anxiety, Poetry anthology of Konser Kecemasan.